Exploring Relative Age Effects in Youth Ice Hockey Through a Single Team Case Study and Composite Narratives - Hancock, David J. (Frontiers in Sports and Active Living, 2021)
Relative age effects (when birthdate influences participation or performance) in sport potentially influence the experiences of sport participants, including athletes, parents, and coaches. Nearly all existing literature on relative age effects adopts a quantitative approach, limiting our understanding of the phenomenon. Thus, the purpose of this unique study was to explore relative age effects using an instrumental, descriptive case study approach with one elite, youth, male ice hockey team. This context was chosen given the high prevalence of relative age effects among such groups. Participants included 20 athletes, 19 parents, and 2 coaches from one team. Data were collected through biometric measures, semi-structured interviews, and participant observations. Results were presented as five composite narratives: relatively older athletes, relatively younger athletes, parents of relatively older athletes, parents of relatively younger athletes, and coaching staff. The narratives demonstrated unique relative age experiences for each group of participants. Discussion aligns the results with the social agents model that explains relative age effects. Practical recommendations for sport participants are also provided.